EVALUASI KINERJA PROSES PENINGKATAN MUTU BATUBARA (COAL UPGRADING) MELALUI PENGUJIAN BERBAGAI BATUBARA PERINGKAT RENDAH DARI KALIMANTAN - Yusnitati Yusnitati (Jurnal Energi dan Lingkungan (Enerlink), 2011)
The upgrading of Indonesian low rank coal from Kalimantan was performed using a slurry dewatering process in a stirred batch autoclave (inner volume of 5 liters) equipped with a condenser, a pressure control valve(PCV), and a receiver. The slurry dewatering process runs were carried out under condition at 3.5 kg/cm2G of nitrogen pressure, 250oC of heater temperature and 150 rpm of agitator speed. Kerosene and low sulfur waxy residue (LSWR) were used as oil solvent. The fluidity of slurry was studied with the ratio of oil to coal (O/C) at 1.5 to 2 wt/wt and the concentration of LSWR at 0.5 to 2% in oil. The temperature profile during the operation was evaluated to understand process performance. Moreover, the pH, TSS, TDS content in water product was analyzed. A centrifuge separator (cap. 200 gram, 1000 rpm) was used in order to remove oilin coal slurry. It was found that calorific value as received basis has increased sharply from 5,178 kcal/kg to 7342 kcal/kg, following the reduction of total moisture drastically after upgrading from 25,5% to 4,97%. The content of ash, volatile matter and the elemental analysis do not change very much from that of raw coal. This phenomenon shows that no chemical reaction occurs in the process and almost all added oil could be recovered. It can be expected that the O/Cratio of slurry, which affects the process economic, is lowered to about 1.4 with O/C feed at 2 and LSWR concentration at 0.5%wt. The wastewater from the process is clean enough thereby it needs a simple wastewater treatment unit in commercial plant. Reabsorption test showed that stable moisture contentin coal has achieved at 7.5 wt% for 13 days. The temperature profile suggested that the slurry dewatering process could be applied effectively for Indonesianlow rank coal with excellent characteristics.Kata Kunci:batubara muda, slurry dewatering, upgrading